FUCOIDAN FROM Fucus vesiculosus, REGULATES OXIDATIVE AND TRANSCRIPTIONAL RESPONSES IN THE SULFOXAFLOR EXPOSED MICE LIVER: ASSESMENT OF DNA DAMAGE GENES, THAT REPAIR DNA DAMAGE (XRCC1, OGG1, APE1, AND PARP1), AND THE ANTIOXIDANT STATUS - Petek Piner Benli; Yusuf Kenan Daglioglu; Cagil Coskun (Journal of Animal and Plant Sciences, 2025)
This research aimed to determine regulatory role ofsulfated polysaccharides fucoidan from Fucus vesiculosus against oxidative and transcriptional responses in sulfoxaflor exposed mice liver. For this purpose both sulfoxaflor and fucoidan were given orally to mice for 24 hours and 7 days at doses of 15 mg/kg/day (equivalent to 1/50 oral LD50) and 50 mg/kg/day. At the end of the tests, liver samples were collected and used to assess 8-OHdG levels, the mRNA expression levels of DNA damage response genes such as XRCC1, OGG1, APE1, and PARP1. Furthermore, levels of tGSH and enzyme activity of GPx, GR, and GST, as well as TBARS, were also examined. The current study's findings demonstrated that acute sublethal exposure to sulfoxaflor caused lipid and DNA damage in mice liver via raising TBARS and 8-OHdG levels, respectively, and activating antioxidants linked to GSH. Furthermore, sulfoxaflor increased the mRNA expression of XRCC1 and APE1 genes, which are involved in the DNA repair mechanism. This tudy indicated that sulfoxaflor caused oxidative responses via increasing 8-OHdG and TBARS levels and altering the antioxidant status. Fucoidan protected liver cells from sulfoxaflor-induced oxidative effects and regulated the DNA damage response at the transcriptional level in mice liver.
Keywords: Fucoidan; Sulfoxaflor; DNA damage; DNA repair genes; antioxidant status